POTASSIUM DOSES AND APLICATION FORNS IN COMMON BEANS IN NO TILLAGE SYSTEM - Sguario Jr., José Carlos; Daros, Edelclaiton; Pauletti, Volnei; Ronzelli Jr., Pedro; Soares-Koehler, Henrique; Oliveira, Ricardo Augusto de (Scientia Agraria, 2006)
In 1997/98 and 1998/99 experiments were implanted in field in Tibagi, PR, to evaluate the answer of the common beans at the different potassium rates (0, 30, 60, 90 and 120 kg ha-1 of K2O) and two application forms (line and throw), in Cultivar Carioca in notill system. The experiment was installed in randomized blocks in arrangement factorial 2x5 with four replications. In the stages R5, R6, R7, R8 e R9 they were used ten plants and evaluated dry mass. The leaves of twenty plants were collected to observe the potassium level in the leaf tissue. In the two years of evaluation, the culture didn’t answer to the different potassium doses and the two application forms to the yield and its components, showing that, even for high yields, favorable climatic conditions, the plant supplies its need for the element in the soil, due constant replacement of the cultures predecessors, cultural remains.